The Rumanian Orthodox church and the west - Tappe, Eric Ditmar (Studies in church history, 1976)
The title of this paper raises a problem at the very outset. What is meant by ‘the Rumanian Orthodox church’ when one is talking of a period before the notion of ‘Rumania’ had been conceived? In this paper it will be taken to mean the Orthodox church as it existed in the principalities of Wallachia, Moldavia and Transylvania from the fourteenth century and has continued in those territories to the present day.A few words first about the prehistory of the Rumanian Orthodox church as thus defined. The Roman province of Dacia had been created by Trajan in AD 106, and the administration had been withdrawn south of the Danube by Aurelian in 271, after which the territories in question were controlled first by the Goths and then by a succession of other invaders for about ten centuries. During this millenium they remain for us in a darkness lit by very few rays. It is therefore not surprising that there is little evidence for church organisation north of the Danube during this period, especially when we remember that the Dacian lands ceased to belong to the empire half a century before Christianity became a tolerated religion. The first church building so far discovered in the lands north of the lower Danube is at Sucidava, a bridgehead held by the Romans after their withdrawal, destroyed by the Huns in 447, and refounded by Justinian in his first years as emperor. This basilica is apparently from Justinian’s time, and being in a bridgehead, may be presumed to have depended on a church organisation south of the Danube.